Analisis Mekanisme Pembiayaan Pada Tabungan Asuransi Dana Haji Produk Mitra Mabrur (Studi Kasus : AJB Bumiputera 1912 Syariah Cabang Medan) - Yolanda Tawabina; Rahmi Syahriza (Jurnal Manajemen Akuntansi (JUMSI), 2022)
AbstractThis research aims to determine how the financing mechanism for Hajj fund insurance savings at AJB Bumiputera 1912 Sharia Division and the advantages and disadvantages of MitraMabrur products.  Type of the research used descriptive qualitative research.  The results of the researchshowed that in general the financing mechanism for Hajj fund insurance savings starts from the requirements for submission, operational systems, fund management and distribution of investment returns. Of all the processes implemented by AJB Bumiputera 1912 the Sharia Division is quite simple and easy. The advantage of the MitraMabrur product is that participants can take cash value from ongoing premiums. The weakness of this product is that the company does not prepare BPIH, does not register participants in the SISKOHAT application and there is no certainty of participant departure.